1994
DOI: 10.1002/dc.2840110205
|View full text |Cite
|
Sign up to set email alerts
|

Simplified nuclear grading of fine‐needle aspirates of breast carcinoma: Concordance with corresponding histologic nuclear grading and flow cytometric data

Abstract: Although histologic grading of breast carcinoma is widely practiced by most pathologists, cytologic grading of fine-needle aspirates (FNA) of this neoplasm is not commonly done. This study addresses the issue of the accuracy of a new classification system, a simplified Nuclear Grading (NG) system based on the criteria proposed by Black et al. (Surg Gynecol Obstet 1955;100:543) in FNA of breast carcinoma. We reviewed 100 cases of breast carcinoma, initially diagnosed by fine-needle aspiration biopsy (FNAB) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 15 publications
(1 reference statement)
0
30
0
3
Order By: Relevance
“…Várias classificações cito-prognósticas têm sido propostas, aplicáveis para preparados citológicos e histológicos [8][9][10][11][12]18,19 . Algumas classificações baseiam-se em critérios exclusivamente nucleares, enquanto outras associam aspectos arquiteturais e nucleares.…”
Section: Métodos: a Avaliação Da Concordância Cito-histológica Foi Reunclassified
See 2 more Smart Citations
“…Várias classificações cito-prognósticas têm sido propostas, aplicáveis para preparados citológicos e histológicos [8][9][10][11][12]18,19 . Algumas classificações baseiam-se em critérios exclusivamente nucleares, enquanto outras associam aspectos arquiteturais e nucleares.…”
Section: Métodos: a Avaliação Da Concordância Cito-histológica Foi Reunclassified
“…Para graduação nuclear foram utilizadas nos esfregaços três classificações citológicas que apresentam apenas critérios nucleares: sistema de Black modificado por Fisher et al 21 (BM), sistema de Black simplificado (BS) 10,12 e classificação de Hunt 9 . Essas classificações foram comparadas com o sistema de graduação nuclear de Black modificado por Fisher et al 21 , utilizado para avaliação dos cortes histológicos.…”
Section: Materiais E Métodosunclassified
See 1 more Smart Citation
“…Recently a few studies showed that tumor grading of fine needle aspirates of breast carcinoma correlates well with histologic grading and is highly reproducible. 3,4,6,7,12 However, tumor grading of breast aspirates is not routinely practiced, especially by private practice pathologists. Possible explanations are the lack of truly objective criteria and the lack of participation by private practice pathologists themselves in studies performed by university-based pathologists.…”
mentioning
confidence: 99%
“…3,4,6,7,12 Based on these studies, the grading system most applicable to cytology is the MB nuclear grading system, originally proposed by Fisher et al 9,10 The MB system is based solely on cytologic features-namely, nuclear pleomorphism, delicacy of chromatin strands, presence or absence of nucleoli, and number of mitotic figures. Because of these cytologic criteria, it has been shown that the MB grading system has a very high correlation with histology and is highly reproducible.…”
mentioning
confidence: 99%